Deranged Calcium Signaling and Neurodegeneration in Spinocerebellar Ataxia Type 2 - Liu, Jing (Society for Neuroscience, 2009)
Spinocerebellar ataxia type 2 (SCA2) is an autosomal dominantly inherited, neurodegenerative disease caused by an expansion of polyglutamine tracts in the cytosolic protein ataxin-2 (Atx2). Cerebellar Purkinje cells (PCs) are predominantly affected in SCA2. The cause of PC degeneration in SCA2 is unknown. Here we demonstrate that mutant Atx2–58Q, but not wild-type (WT) Atx2–22Q, specifically associates with the cytosolic C-terminal region of type 1 inositol 1,4,5-trisphosphate receptor (InsP(3)R1), an intracellular calcium (Ca(2+)) release channel. Association with Atx2–58Q increased the sensitivity of InsP(3)R1 to activation by InsP(3) in planar lipid bilayer reconstitution experiments. To validate physiological significance of these findings, we performed a series of experiments with an SCA2–58Q transgenic mouse model that expresses human full-length Atx2–58Q protein under the control of a PC-specific promoter. In Ca(2+) imaging experiments, we demonstrated that stimulation with 3,5-dihydroxyphenylglycine (DHPG) resulted in higher Ca(2+) responses in 58Q PC cultures than in WT PC cultures. DHPG-induced Ca(2+) responses in 58Q PC cultures were blocked by the addition of ryanodine, an inhibitor of the ryanodine receptor (RyanR). We further demonstrated that application of glutamate induced more pronounced cell death in 58Q PC cultures than in WT PC cultures. Glutamate-induced cell death of 58Q PC cultures was attenuated by dantrolene, a clinically relevant RyanR inhibitor and Ca(2+) stabilizer. In whole animal experiments, we demonstrated that long-term feeding of SCA1–58Q mice with dantrolene alleviated age-dependent motor deficits (quantified in beam-walk and rotarod assays) and reduced PC loss observed in untreated SCA2–58Q mice by 12 months of age (quantified by stereology). Results of our studies indicate that disturbed neuronal Ca(2+) signaling may play an important role in SCA2 pathology and also suggest that the RyanR constitutes a potential therapeutic target for treatment of SCA2 patients.